2010
DOI: 10.1007/s00405-010-1300-5
|View full text |Cite
|
Sign up to set email alerts
|

New approach to diagnose arytenoid dislocation and subluxation using three-dimensional computed tomography

Abstract: Understanding the complex three-dimensional (3D) arrangement of the arytenoid cartilage is necessary for diagnosing arytenoid dislocation (AD) and arytenoid subluxation (AS). We examined the 3D arrangements of AD and AS (AD/AS) cases by region and considered their new diagnoses. This retrospective study included 2 patients with AD, 10 with AS, and 23 with unilateral vocal fold paralysis (UVFP) for comparison. The etiologies were intubation-induced and idiopathic. We classified the AD/AS position into four join… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 12 publications
0
31
0
2
Order By: Relevance
“…We previously divided the cricoid facet into cranial and caudal parts along the cylindrical long axis of the facet. 9,10 Notably, if the arytenoid cartilage glided caudally, it moved anteriorly at the same time. First, we examined the position of the arytenoid cartilage of the CAJ during comfortably pitched phonation to compare that during the high-pitched phonation.…”
Section: Materials and Methods Patientsmentioning
confidence: 98%
See 2 more Smart Citations
“…We previously divided the cricoid facet into cranial and caudal parts along the cylindrical long axis of the facet. 9,10 Notably, if the arytenoid cartilage glided caudally, it moved anteriorly at the same time. First, we examined the position of the arytenoid cartilage of the CAJ during comfortably pitched phonation to compare that during the high-pitched phonation.…”
Section: Materials and Methods Patientsmentioning
confidence: 98%
“…In 3DCT studies of unilateral vocal fold paralysis (UVFP), we also reported that the arytenoid cartilage on the healthy side moved toward the medial (during phonation) and lateral (during rest) parts of the CAJ in a rocking movement, and that the arytenoid cartilage was located toward the caudal part of the CAJ during both rest and phonation. 9,10 However, the normal state of phonation is not necessarily being observed because the opposite side is paralyzed and the arytenoid cartilage on the healthy side is likely to be overadducted during phonation. Additionally, many issues remain unclear, such as how the presence of a gliding movement in the arytenoid cartilage as a result of a change in the phonation condition (eg, high-pitched phonation) affects vocal fold elongation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reduced vocal fold mobility, vocal fold high mismatch, vocal fold length differences, an absent Bjostle^sign and arytenoid edema are all suggestive of arytenoid dislocation [15]. A CT with fine cuts through the larynx can also be helpful [16]. Definitive diagnoses can be made with laryngeal EMG and palpation of the arytenoid under suspension laryngoscopy [14••].…”
Section: Introductionmentioning
confidence: 99%
“…Autologous tissue, allogeneic, artificial materials and tissue engineering technology were utilized to repair and reconstruct laryngeal cartilage damage [3]. At present, natural macromolecule biomaterials, synthetic polymer materials, bioceramic materials and composites have been the primary materials for tissue engineering scaffolds [4][5][6][7][8]. Natural biological materials possess excellent adhesion for cells, hydrophilicity and compatibility, which include gelatin, sodium alginate, collagen, chitosan, and fibrin gels.…”
Section: Introductionmentioning
confidence: 99%